(3hGSWI GdSdhc aj SjGSI Gdedhcs - (3ehSi (B((3GdKGfj(B) (3Hf jhSa CHj jYbhH Hf YHO GdQMef Hf jMji Hf jZeQGSf Hf RjGf, CHhMeh, hjbGd CHhMGeje,J (B791 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd fYeJg Ydi GdNdb HeG Cdage Ydjg ef GdMb CeG HYO aEfg deG cGfJ GdChdGO bWY GdCcHGO hYeGO GdXghQ s
(3BNQgG (B:s
(3aGYed jG Hfi HhUjJi JSYO hGMaXgG JQTO hdG Mhd hdG bhI EdG HGddg s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B331s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdSjGSI hGdGLJeGYs